Sociology Informed By History And Culture: Involving, Resources Of Social History Of Nepal - Mana Hari Dhakal, (Journal of Contemporary Review, 2025)
This article explores the relationship between history and cultural resources of Nepal. By situating social action and social structures in their historical contexts and by examining their historical unfolding, historical Sociologists exploit the temporality of social life to ask and answer questions of perennial importance to social theory. The last period of the Lichchhavi period after the origin of the Nepal Valley is called the ancient period. In terms of time, the period before 936 BC is called the ancient period. This period is the time of classification of Nepalese history and culture. Since it was a country ruled by named Ne, its name has remained Nepal. The history of Nepal has accepted that the Nepalese are capable of hard work and hard work. Based on various historical sources, Nepal was a safe fortress. After the reign of Gopal, Mahispala Kirant, Lichchhavi, Malla and Shah dynasty, a republic is currently being practiced in Nepal, but it is not complete. Since a republican constitution has not been formed, it is not possible to predict what its future will be. The settlement of the Kathmandu Valley and the system of government at that time were appropriate according to the time, but due to political changes, there was a change in the dynasty but the system did not change. Circumstances and power were important in the fall of the Kirant dynasty, which had been successful in ruling for a long time. In Nepal, before 1981, the subjects of sociology/anthropology were studied indirectly in history, and social history has emerged as a teaching method for society. Baburam Acharya's Brief History of Nepal. Willam karkpatrick, Krishna Bahadur Thapa, Tulsiram Vaidhe, Triratna Manandhar have written the social history of Nepal. Since before 1981, the study of Nepali society was done in history, the science of studying society developed as a separate discipline in Nepal. Social history shows that the study of history, art, literature, and culture has shifted from the study of history to sociology. History is the past, it includes the civilization, culture, and society of a country. All subjects have a history. The past of sociology is also history.